Clinical Utility of Concurrent Single-Nucleotide Polymorphism Microarray on Fresh Tissue as a Supplementary Test in the Diagnosis of Renal Epithelial Neoplasms. Issue 5 (1st November 2015) - Hamilton, Heidi H.; McDermott, Annie; Smith, M. Timothy; Savage, Stephen J.; Wolff, Daynna J.
Abstract: Objectives: The histologic and immunohistochemical variability of renal epithelial tumors makes classification difficult; with significant clinical implications, efforts to make the proper diagnoses are necessary. Single-nucleotide polymorphism (SNP) microarray analysis has been proposed as a supplementary study for the classification of renal epithelial neoplasms; however, its practical use in the routine clinical setting has not been explored. Methods: Surgical pathology cases that were classified histologically as renal epithelial tumor subtypes and had concurrent SNP microarray were retrospectively reviewed to correlate tumor morphology and SNP microarray results. Results: Of the 99 cases reviewed, 88 (89%) had concordant histologic and microarray results. Four (4%) cases were unclassifiable by microarray due to uncharacteristic chromosomal abnormalities. Seven (7%) of the 99 cases had discordant microarray and histologic diagnoses, and following review of the histology, the diagnoses in two of these cases were subsequently changed. Conclusions: For most cases, concurrent SNP microarray confirmed the histologic diagnosis. However, discrepant microarray results prompted review of morphology and further ancillary studies, resulting in amendment of the final diagnosis in 29% of discrepant cases. SNP microarray analysis can be used to assist with the diagnosis of renal epithelial tumors, particularly those with atypical morphologic features.